An extended finite difference method for singular perturbation problems on a non-uniform mesh - Swarnakar, D.; Kumar, V.G.; Soujanya, G.B.S.L. (Zielona Góra: Uniwersytet Zielonogórski)
An extended second order finite difference method on a variable mesh is proposed for the solution of a singularly perturbed boundary value problem. A discrete equation is achieved on the non uniform mesh by extending the first and second order derivatives to the higher order finite differences.
Keywords: non uniform grid; finite difference method; singular perturbation; boundary layer